2015
DOI: 10.1111/iej.12464
|View full text |Cite
|
Sign up to set email alerts
|

The origin of endodontic Enterococcus faecalis explored by comparison of virulence factor patterns and antibiotic resistance to that of isolates from stool samples, blood cultures and food

Abstract: Evidence for a foodborne transmission, explaining the high reported prevalence of E. faecalis in root filled teeth, could not be determined based on the similarities in virulence factor patterns and antibiotic susceptibility. The only linkage between isolates from food and root canals consisted of a shared common combination of the genes gelE, efaA and ace. The high occurrence of putative virulence traits in food isolates questions the safety of E. faecalis in food products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 30 publications
2
13
0
1
Order By: Relevance
“…3,4 A wide armamentarium of natural resistance, along with the capacity to acquire and disseminate multiple antibiotic resistance and virulence determinants in Enterococci is of significant concern with limited therapeutic alternatives. [5][6][7] Concurrent with the declining discovery rate of novel antibiotics, there are some strains of Enterococci have become resistant to last-resort drugs. [8][9][10] In general, Enterococci are considered as a significant antibiotic resistance threat and pose a risk to public health as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 A wide armamentarium of natural resistance, along with the capacity to acquire and disseminate multiple antibiotic resistance and virulence determinants in Enterococci is of significant concern with limited therapeutic alternatives. [5][6][7] Concurrent with the declining discovery rate of novel antibiotics, there are some strains of Enterococci have become resistant to last-resort drugs. [8][9][10] In general, Enterococci are considered as a significant antibiotic resistance threat and pose a risk to public health as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Enterococcus faecalis is an important nosocomial pathogen that has been implicated in oral infections, especially endodontic disease. However, little is known about the relatedness of E. faecalis isolates from different clinical origins, and the source and the role of these microorganisms in oral infection (1,2,3).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of E. faecalis in the root canal system was shown to be associated with the its presence in saliva (10), but an endogenous source has been questioned (11). Zehnder & Guggenheim, 2009 (12), proposed foodborne transmission, but evidence for this could not be provided in the study of Vidana et al 2016 (1) where a large number of oral and food isolates were profiled. In a separate study, the same research group concluded that whilst the potential for nosocomial transmission of enterococci from environmental surfaces in dental surgeries appeared small, further investigation of this was warranted (13).…”
Section: Introductionmentioning
confidence: 99%
“…The spread of the nosocomial VRE occurs and when the immunity is lowered VRE multiply to cause disease. Few studies have shown that antibiotic resistant enterococci is transmitted by food [47][48][49] but recently Vidana et al [50] have said there is no food related transmission of enterococci. Enterococci are now showing a high degree of resistance to tetracycline, chloramphenicol, erythromycin besides vancomycin pose a threat for spread of nosocomial infection particularly in patients of ICUs and on mechanical ventilators [51].…”
Section: Oral Infectionsmentioning
confidence: 99%